Elucidating the relationship between dyslipidemia and osteoporosis: A multicenter, prospective cohort study protocol - Wei, Xu; Zhang, Yili; Sun, Chuanrui; Qi, Baoyu; Huang, Xinyi; Chen, Ming; Liu, Ning; Sun, Kai; Chen, Xin; Qin, Xiaokuan; Xie, Yanming; Zhu, Liguo (Frontiers in Cardiovascular Medicine, 2022)
Backgrounds: Previous study has shown similar factors in dyslipidemias (DL) and osteoporosis (OP). However, no cohort study has been reported on the association between DL and OP in postmenopausal population in China. This study aims to provide epidemiological and pathophysiological evidence regarding the association between DL and bone mass and fracture risk. Methods: This is a multicenter, prospective cohort study that will have approximately 1100 representative participants enrolled from multiple hospitals or communities in China. They will be divided into two groups according to whether or not they are exposed to dyslipidemia and will be epidemiologically investigated. Each participant will be visited continuously once every year with a minimum follow-up of 3 years to track incidences of OP. Meanwhile, free bone density screening, questionnaires and blood sample collection will also be completed during this period. Conclusion: The current study is likely to provide a greater insight into the relationship between lipid metabolism and bone metabolism in postmenopausal women. Furthermore, the research result maybe feed into public health strategies with regard to metabolic disease prevention.